Abuse of the Malaysian elderly: An analysis on the adequacy and suitability of the Domestic Violence Act 1994 (Act 521) to protect the elderly victim - Asiah, Bidin; Jal Zabdi, Mohd Yusoff (2015)
Abuse of the elderly is not a new issue at the international level. It is seen as a serious social problem that is a growing concern. A number of countries have enacted specific legal mechanisms to address and prevent the problem. In Malaysia, the abuse of the elderly is recognized as a form of domestic violence. The legislation dealing with matters pertaining to domestic violence is Domestic Violence Act 1994 (Act 521) which is to be read together with Penal Code. The Domestic Violence Act (DVA) becomes the main legislation which gives protection and provides civil remedies to the abused victims while the Penal Code concerns with penalizing the abuser. Despite the growing literature on the issue of elder abuse in Malaysia, little has been written on the legal protections offered by the DVA to the elderly victims. This paper aims to explore the adequacy of civil remedies given to the abused elderly as provided for under the DVA and further analyses on the adequacy and suitability of the Act in protecting the elderly victims from abuse.